2019
DOI: 10.1590/s0104-12902019180615
|View full text |Cite
|
Sign up to set email alerts
|

Os benzodiazepínicos na ordem dos discursos: de objeto da ciência a objeto gadget do capitalismo

Abstract: Resumo Este estudo objetiva analisar o fenômeno do abuso de benzodiazepínicos, considerando o modo como essa substância comparece nos discursos constituídos na abordagem do mal-estar na contemporaneidade. Trata-se de uma pesquisa descritiva, de natureza qualitativa; foram ouvidos 18 médicos e enfermeiros atuantes na rede de saúde de Fortaleza, além de nove mulheres usuárias dos serviços. A população entre usuários limitou-se ao sexo feminino, devido ao fato de a literatura apontar prevalência do abuso de benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…What is heard in services on a daily basis is that health workers are generally not satisfied with working conditions and resent the demands of users, who often want only the renewal of the prescription and nothing more. In a study on benzodiazepines in another northeastern city, the authors also found this difficulty among health professionals and users (Silveira, Almeida & Carrilho, 2019).…”
Section: Figure 1 Sqr 20 Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…What is heard in services on a daily basis is that health workers are generally not satisfied with working conditions and resent the demands of users, who often want only the renewal of the prescription and nothing more. In a study on benzodiazepines in another northeastern city, the authors also found this difficulty among health professionals and users (Silveira, Almeida & Carrilho, 2019).…”
Section: Figure 1 Sqr 20 Resultsmentioning
confidence: 92%
“…What is implicit in this relationship is that ruling relations can happen in two moments: when the professional, supposedly the one who has the knowledge, has the power to prescribe a "blue recipe" (popular term for psychotropic recipe), and when the nonspecialist user, but with the power to make a scandal in the service when he/she cannot get the medicine, requires this medication or seeks another professional to satisfy it. Parallel to this "demand" of users for medicines, most health workers does not know enough about psychological distress, and do not feel competent enough in this area to provide other care practices (Silveira, Almeida, & Carrilho, 2019). Thus, Bezerra, Morais, Paula, Silva and Jorge (2016) state that the exacerbated consumption of medicines is related to the hegemonic context and to the marketing social production of health, involving different actors, including: doctors, patients, pharmaceutical industry and health regulatory agencies.…”
Section: Figure 1 Sqr 20 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel to this "demand" of users for medicines, most health workers know little about psychological distress, and do not feel competent enough in this area to provide other care practices (Silveira, Almeida & Carrilho, 2019;Azevedo, 2010). Thus, Bezerra et al (2016) state that the exacerbated consumption of medicines is related to the hegemonic and marketing social production of health, involving different actors, including: doctors, patients, pharmaceutical industry and health regulatory agencies.…”
Section: Resultsmentioning
confidence: 99%
“…When seeking health services, many users have nonspecific somatic complaints, which can lead to difficulties in the correct management of these manifestations of suffering. Thus, there is an underdiagnosis and abuse of benzodiazepines and unnecessary examinations and referrals, commonly performed by health professionals (Silveira, Almeida & Carrilho, 2019;Souza et al, 2017).…”
Section: Resultsmentioning
confidence: 99%